DeepCF: A Deep Feature Learning-Based Car-Following Model Using Online Ride-Hailing Trajectory Data. (7th December 2020) - Xie, Yizhen; Ni, Qichao; Alfarraj, Osama; Gao, Haoran; Shen, Guojiang; Kong, Xiangjie; Tolba, Amr
Abstract : The car-following model describes the microscopic behavior of the vehicle. However, the existing car-following models set the drivers' reaction time to a fixed value without considering its dynamics. In order to improve the accuracy of car-following model, this paper proposes Deep Feature Learning-based Car-Following Model (DeepCF), a car-following model based on fatigue driving and Generative Adversarial Networks (GAN). The model is composed of the drivers' reaction time model and the car-following decision algorithm. First, we regard driving fatigue as the starting point to study the influence of driving time and the acceleration of the preceding vehicle on the drivers' reaction time, and develop a coarse-grained drivers' reaction time model. Secondly, considering the impact of fatigue driving on car-following decisions, we utilize GAN to generate a driving decision database based on reaction time and use Euclidean distance as a decision search indicator. Finally, we conduct experiments on a real data set, and the results indicate that our DeepCF model is superior to baseline models.